(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In spite of the number of investigations devoted to gear research and analysis there still remains to be developed, a general numerical approach capable of predicting the effects of variations in gear geometry, contact and bending stresses, torsional mesh stiffness and transmission errors. The objectives of this study are to use a numerical approach to develop stress based on the behavior of the pressure angle of the spur gears in mesh, this is to help to predict the effect of gear tooth stresses